2013
DOI: 10.1021/es303316d
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Residence Times of Semivolatile Organic Compounds: Model Estimation and Field Evaluation

Abstract: Indoor residence times of semivolatile organic compounds (SVOCs) are a major and mostly unavailable input for residential exposure assessment. We calculated residence times for a suite of SVOCs using a fugacity model applied to residential environments. Residence times depend on both the mass distribution of the compound between the "mobile phase" (air and dust particles settled on the carpet) and the "non-mobile phase" (carpet fibers and pad) and the removal rates resulting from air exchange and cleaning. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 52 publications
0
66
1
Order By: Relevance
“…We had questionnaire information on weekly chore frequency and duration, which may correlate with outdoor activities, but additional investigation of these variables with respect to employment status did not reveal any noteworthy relationships (data not shown). It is also possible that unemployed women spend more time inside the home where OP insecticides may persist due to protection from moisture, sunlight, and other conditions that lead to chemical degradation (Shin et al, 2013), or have differences in diet and sources of food relative to employed women, which influence exposure. Although Yolton et al (2013) reported a relationship that was opposite of our study findings (unemployed women had lower OP metabolite urinary concentrations than other women), which may reflect differences in occupational exposures between pregnant women living in Cincinnati versus Puerto Rico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had questionnaire information on weekly chore frequency and duration, which may correlate with outdoor activities, but additional investigation of these variables with respect to employment status did not reveal any noteworthy relationships (data not shown). It is also possible that unemployed women spend more time inside the home where OP insecticides may persist due to protection from moisture, sunlight, and other conditions that lead to chemical degradation (Shin et al, 2013), or have differences in diet and sources of food relative to employed women, which influence exposure. Although Yolton et al (2013) reported a relationship that was opposite of our study findings (unemployed women had lower OP metabolite urinary concentrations than other women), which may reflect differences in occupational exposures between pregnant women living in Cincinnati versus Puerto Rico.…”
Section: Discussionmentioning
confidence: 99%
“…Direct use of pesticides by the participant creates opportunities for exposure. Because OP insecticides are fairly persistent indoors (Shin et al, 2013), there are also opportunities for exposure long after the product has been applied. The associations identified with being married and the other home pest-related issues are difficult to explain and are perhaps chance findings.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed explanations of the extraction, cleanup, and analysis procedures for PBDE analysis are published elsewhere (Clifton et al, 2013; Shin et al, 2013). Briefly, dust samples were sieved to ≤150 µm and extracted using accelerated solvent extraction.…”
Section: Methodsmentioning
confidence: 99%
“…These levels are much higher than the levels seen on the compacted red clay floors in both Nepali villages in this study, where the maximum level of methyl parathion was 532 ng/m 2 . Carpet has been identified as a reservoir that can slow the removal of semivolatile organic compounds [58] such as methyl parathion, and as a source of increased particulate matter exposure when compared to bare floors [59]. In the rural Nepali homes in this study, the compacted red clay floors were cleaned with brooms, and floors were regularly re-mudded once per year during festival times.…”
Section: Discussionmentioning
confidence: 99%